2021
DOI: 10.5194/isprs-archives-xlvi-4-w5-2021-565-2021
|View full text |Cite
|
Sign up to set email alerts
|

Layout Plan Analysis on Urban Pathways, Nodes and Edges in Kuala Muda Fishing Village

Abstract: Abstract. This paper studies three urban design elements, namely pathways, nodes, and edges, in Kampung Kuala Muda, Penaga, a traditional fishing village in Penang. The case study portrays the resistance of a fishing settlement by exhibiting a unique local culture of whispering auction market that is celebrated by many, including locals and tourists. The study of the paths, edges, and nodes of the case study is carried out by applying a qualitative method and data collection through a site visit, informal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Phaksopa et al (2021) reported a high abundance of fibre recovered from fishing ground in Thailand, supporting that the degradation of fishing gear can significantly contribute to fibre enrichments in aquatic environments. It is ecologically important that a low abundance of MPs were reported in both sites as they supply substantial amounts of seafood to neighbouring states (Zairudin et al, 2021). This would ensure the food safety for human consumption because seafood is one of the crucial sources of protein in Malaysian households (Karbalaei et al, 2019).…”
Section: Abundance and Distributionmentioning
confidence: 99%
“…Phaksopa et al (2021) reported a high abundance of fibre recovered from fishing ground in Thailand, supporting that the degradation of fishing gear can significantly contribute to fibre enrichments in aquatic environments. It is ecologically important that a low abundance of MPs were reported in both sites as they supply substantial amounts of seafood to neighbouring states (Zairudin et al, 2021). This would ensure the food safety for human consumption because seafood is one of the crucial sources of protein in Malaysian households (Karbalaei et al, 2019).…”
Section: Abundance and Distributionmentioning
confidence: 99%